Joining up in the Second World War - Morley, Joel (Manchester University Press, 2025)
Joining Up connects the First and Second World Wars by examining how the cultural legacy of the First World War affected young men’s attitudes to service and subjective conceptions of wartime masculinity during the Second World War. It uses original and archival oral histories and the Mass Observation Archive to explore how young men in inter-war Britain encountered and understood representations of the Great War in popular culture and day-to-day-life. By demonstrating the breadth of representations through which the cultural memory of the Great War was transmitted and the diversity of young men’s responses, Joining Up makes a significant intervention in the cultural history of the Great War, and interactions with Great War veterans are shown to be more important than previously acknowledged. Joining Up also adds new depth to understandings of Second World War enlistment and masculinity. It shows that British men had varied attitudes and explores why. Most were reluctant servicemen, but compliance with conscription was increased by a manpower system that gave men some agency over how they served. Understandings of the Great War informed men’s attitudes and service preferences, commonly discouraging service in the Army. Nevertheless, some enthusiastically anticipated service, especially if they hoped to join the RAF. Men’s subjective conceptions of wartime masculinity are shown to be diverse. Long-standing constructions of military masculinity were durable, and often reinforced by representations of the Great War, and men’s conceptions of wartime masculinity often diverged from the temperature masculinity that dominated public discourse.